Latent tuberculosis infection (LTBI) in health-care workers: a cross-sectional study at a northern Peruvian hospital - Meregildo-Rodriguez, Edinson Dante; Yuptón-Chávez, Verónica; Asmat-Rubio, Martha Genara; Vásquez-Tirado, Gustavo Adolfo (Frontiers in Medicine, 2023)
Background: Health-care workers (HCWs) have a higher risk of latent tuberculosis infection (LTBI) and active tuberculosis than the general population. In HCWs, the risk of tuberculosis infection depends on the local tuberculosis prevalence, HCWs' characteristics, the health-care facility, and prevention and control measures. We aimed to estimate the prevalence and risk factors for LTBI in HCWs at a northern Peruvian hospital. Method: This had two phases: 1) a cross-sectional phase involving recruitment, history taking, and sampling for the Interferon-Gamma Release Assays (IGRA test), and 2) a prospective follow-up of IGRA-positive participants. We enrolled direct and non-direct patient caregivers among HCWs. We defined an LTBI case if the IGRA test was positive and clinical, laboratory, and radiological evaluations for active tuberculosis were negative. Results: We recruited 308 participants between November 2022 and May 2023. The mean age was 38.6 ± 8.3 years. Over 75% of the participants were female. The most common job category was technicians (30.5%), physicians (22.7%), nurses (20.5%), and other HCWs groups (17.5%). Most participants worked in hospital wards (28.2%), diagnostics departments (16.9%), and critical care departments (15.6%). The LTBI prevalence among HCWs was 17.86% (95% CI 13.84-22.70). In multivariate analysis, after adjusting for age, time working in our hospital, and family history of tuberculosis, males had a higher risk of LTBI (aPR 1.69, 95% CI 1.01-2.77) than females. Working for more than ten years increased the risk of LBTI (aPR 2.4, 95% CI 1.44-3.97) compared to working for ≤10 years). Even further, participants who had worked for more than 20 years had an aPR of 4.31 (95% CI 1.09-13.65) compared to those with ≤ 10 years. Similarly, occupational exposure increased the risk of LTBI (aPR 2.21, 95% CI 1.27-4.08) compared to those HCWs not occupationally exposed. Conclusion: The LTBI prevalence in HCWs at a northern Peruvian hospital was lower compared to other Peruvian cities. Males, more experienced, and occupational exposed HCWs are at higher risk of LTBI. LTBI prevalence in Peruvian HCWs is still high. More studies are needed to address some aspects this study has not examined.